Diagnostic yield and financial implications of a nationwide electrocardiographic screening programme to detect cardiac disease in the young. Issue 8 (11th February 2021) - Dhutia, Harshil; Malhotra, Aneil; Finocchiaro, Gherardo; Parpia, Sameer; Bhatia, Raghav; D'Silva, Andrew; Gati, Sabiha; Mellor, Greg; Narain, Rajay; Chandra, Navin; Behr, Elijah; Tome, Maite; et al.
Abstract: Aims: There is limited information on the role of screening with electrocardiography (ECG) for identifying cardiovascular diseases associated with sudden cardiac death (SCD) in a non-select group of adolescents and young adults in the general population. Methods and results: Between 2012 and 2014, 26 900 young individuals (aged 14–35 years) were prospectively evaluated with a health questionnaire and ECG. Individuals with abnormal results underwent secondary investigations, the costs of which were being based on the UK National Health Service tariffs. Six hundred and seventy-five (2.5%) individuals required further investigation for an abnormal health questionnaire, 2175 (8.1%) for an abnormal ECG, and 114 (0.5%) for both. Diseases associated with young SCD were identified in 88 (0.3%) individuals of which 15 (17%) were detected with the health questionnaire, 72 (81%) with ECG and 2 (2%) with both. Forty-nine (56%) of these individuals received medical intervention beyond lifestyle modification advice in the follow-up period of 24 months. The overall cost of the evaluation process was €97 per person screened, €17 834 per cardiovascular disease detected, and €29 588 per cardiovascular disease associated with SCD detected. Inclusion of ECG was associated with a 36% cost reduction per diagnosis of diseases associated with SCD compared with the health questionnaire alone. Conclusion: The inclusion of an ECG to a health questionnaire is associated with a five-fold increase in the ability to detect disease associated with SCD in young individuals and is more cost effective for detecting serious disease compared with screening with a health questionnaire alone. Graphical Abstract: